2022
DOI: 10.3892/mmr.2022.12835
|View full text |Cite
|
Sign up to set email alerts
|

CTPS cytoophidia formation affects cell cycle progression and promotes TSN‑induced apoptosis of MKN45 cells

Abstract: Cytidine triphosphate synthase (CTPS) forms filamentous structures termed cytoophidia in numerous types of cell. Toosendanin (TSN) is a tetracyclic triterpenoid and induces CTPS to form cytoophidia in MKN45 cells. However, the effects of CTPS cytoophidia on the proliferation and apoptosis of human gastric cancer cells remain poorly understood. In the present study, CTPS-overexpression and R294D-CTPS mutant vectors were generated to assess the effect of CTPS cytoophidia on the proliferation and apoptosis of gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…[ 83 ] The transcription of cell proliferative genes begins with the nuclear translocation of p‐ERK. [ 84,85 ] In agreement with the current results, Said et al, [ 43 ] found a high proliferation rate of prostate in TST‐induced BPH, that was weakened by the inhibition of the ERK1/2 signaling pathway. [ 83 ] On the other hand, ERK1/2 activation inhibited apoptotic signaling by Fas and TRAIL receptors, which can explain the low expression of proapoptotic Bax.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[ 83 ] The transcription of cell proliferative genes begins with the nuclear translocation of p‐ERK. [ 84,85 ] In agreement with the current results, Said et al, [ 43 ] found a high proliferation rate of prostate in TST‐induced BPH, that was weakened by the inhibition of the ERK1/2 signaling pathway. [ 83 ] On the other hand, ERK1/2 activation inhibited apoptotic signaling by Fas and TRAIL receptors, which can explain the low expression of proapoptotic Bax.…”
Section: Discussionsupporting
confidence: 91%
“…[ 83 ] On the other hand, ERK1/2 activation inhibited apoptotic signaling by Fas and TRAIL receptors, which can explain the low expression of proapoptotic Bax. [ 26,84,86 ] In parallel with these results, low apoptotic bodies were well detected in TST‐induced BPH experimental models. [ 60,66 ]…”
Section: Discussionmentioning
confidence: 59%